2014
DOI: 10.7314/apjcp.2014.15.15.6363
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Actinidia Valvata Dunn Extract on N-methyl-N'-nitro-N-nitrosoguanidine-induced Gastrointestinal Cancer in Rats

Abstract: Asian Pac J Cancer Prev, 15 (15), [6363][6364][6365][6366][6367] Introduction Gastric cancer remains a major global problem. In 2008, 989,600 new stomach cancer cases and 738,000 deaths occurred, accounting for 8% of the total cases and 10% of total deaths, respectively (Jemal et al., 2011). Notwithstanding the global declining incidence of gastric cancer, mortality is continuously rising in Asian countries (Hu et al., 2004). Surgery is considered as the gold standard for localized gastric cancer, but most cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Among all the established animal models of gastric cancer (68), the rat model induced with chemical carcinogens such as N -methyl- N '-nitro- N -nitrosoguanidine (MNNG) is widely used due to the simple operation, cheap cost, easy keep and lower natural cancer rate (9). It has been shown that MNNG treatment results in the mutation of DNA and increased oxidative injury, which is critical to gastric carcinogenesis (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Among all the established animal models of gastric cancer (68), the rat model induced with chemical carcinogens such as N -methyl- N '-nitro- N -nitrosoguanidine (MNNG) is widely used due to the simple operation, cheap cost, easy keep and lower natural cancer rate (9). It has been shown that MNNG treatment results in the mutation of DNA and increased oxidative injury, which is critical to gastric carcinogenesis (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…The review of the literature shows that MNNG is used in different doses and for different durations to develop a cancer model. For example, Wang et al 18 reported that they induced gastrointestinal cancer in rats mixing MNNG with their drinking water for 24 weeks. In an earlier study, we used a similar dose of MNNG over a similar period to induce cancer in rats 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that the overexpression of cyclin D1 may result in a reduction of the G1 phase of the cell cycle (15)(16)(17), leading to progression into the S phase and completing the duplication of DNA. The increase in the protein expression of cyclin D1 is observed in certain primary malignant tumors, including parathyroid adenoma, neck squamous-cell carcinoma, breast cancer, esophageal cancer, and hepatocellular carcinoma (18)(19)(20)(21). As MAPK is expressed as an upstream gene of cyclin D1, the increase in the level of p-MAPK in osteosarcoma was directly proportional to the intensity of cyclin D1-positive staining.…”
Section: Discussionmentioning
confidence: 99%